1999
DOI: 10.1046/j.1365-2400.1999.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative life‐history characteristics of native and hatchery‐reared brown trout, Salmo trutta L., in a sub‐Alpine reservoir

Abstract: Wild and non‐native hatchery‐reared brown trout, Salmo trutta L., released when 2 summers old, were caught in the littoral habitat of Vinstervatna Reservoir, southern Norway. Hatchery‐reared brown trout grew more slowly and had a smaller asymptotic length (293 ± 71 mm CL) than native fish (391 ± 56 mm CL). Hatchery‐reared brown trout also exhibited significantly shorter life spans than native fish. This category consisted mainly of individuals aged 2+ and 3+ years, and only 1.5% of the specimens were aged ≥5 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…The proportion of stocked fish was higher among younger fish (age 1+ to 3+) than catchable size fish (age 4+ to 10+). A similar result was found in brown trout from another regulated lake in the same watershed (Hesthagen et al. 1999).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The proportion of stocked fish was higher among younger fish (age 1+ to 3+) than catchable size fish (age 4+ to 10+). A similar result was found in brown trout from another regulated lake in the same watershed (Hesthagen et al. 1999).…”
Section: Discussionsupporting
confidence: 83%
“…The proportion of stocked fish was higher among younger fish (age 1+ to 3+) than catchable size fish (age 4+ to 10+). A similar result was found in brown trout from another regulated lake in the same watershed (Hesthagen et al 1999). If stocked fish are unlikely to reach catchable size but constitute a relatively large fraction of younger fish, they may negatively affect growth and survival of young native conspecifics.…”
Section: Discussionsupporting
confidence: 75%
“…Trout stocked in PAL are reared apart from the lake and released directly into the lake, thus lacking olfactory cues from their relative’s native tributary. O’Grady (1984) and Hesthagen et al. (1999) have previously reported that trout released directly into a lake may have reduced spawning runs into rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Biological aspects such as growth, growth curve, reproduction, first maturity, fecundity, habitat use, sex ratio, and feeding characteristics in resident and sea trout have been studied in streams and lakes in Europe (Jonsson and Sandlund, 1979;Lobon-Cervia et al, 1986;Jonsson, 1989;Haugen and Rygg, 1996;Hesthagen et al, 1999;Nicola and Almodovar, 2002;Hesthagen et al, 2004), in North America (Mcfadden and Cooper, 1962;Beard and Carline, 1991) and in New Zealand (Allen, 1951).…”
Section: Introductionmentioning
confidence: 99%